2019
DOI: 10.1139/apnm-2018-0575
|View full text |Cite|
|
Sign up to set email alerts
|

The performance and aerobic endurance effects of high-intensity versus moderate-intensity continuous running

Abstract: The aim of the present study was to investigate the performance and aerobic endurance effects of high-intensity (HICR) versus moderate-intensity continuous running (MICR), which were nonmatched for total work. Twenty healthy recreational athletes (aged 28 ± 5 years) were randomly assigned to an HICR, MICR, or no-intervention control (C) group. The HICR group (n = 7) performed a 20-min strenuous, almost exhausting, run above lactate threshold (LT) at ∼88% of maximal heart rate (HRmax), whereas the MICR group (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…Our study demonstrates that endurance training increased VO 2 max by 5% only in the IET but not in the MET group, indicating that a moderate endurance training program is sufficient to maintain VO 2 max but not to improve it. The slight increase in VO 2 max associated with the small decrease in HRmax can be attributed partly to hypervolemia induced by increases in cardiac stroke volume due to the training [ 33 , 34 , 35 , 36 , 37 ]. Another study [ 38 ] suggested that improvement in VO 2 max after endurance training was attributed to increases in cardiac output.…”
Section: Discussionmentioning
confidence: 99%
“…Our study demonstrates that endurance training increased VO 2 max by 5% only in the IET but not in the MET group, indicating that a moderate endurance training program is sufficient to maintain VO 2 max but not to improve it. The slight increase in VO 2 max associated with the small decrease in HRmax can be attributed partly to hypervolemia induced by increases in cardiac stroke volume due to the training [ 33 , 34 , 35 , 36 , 37 ]. Another study [ 38 ] suggested that improvement in VO 2 max after endurance training was attributed to increases in cardiac output.…”
Section: Discussionmentioning
confidence: 99%
“…The different findings between the present study (maintained absolute VO 2max ) and the study by Sandbaek et al (1997) (decreased absolute VO 2max in two of three participants) may be due to the use of different test methods (ski treksimulated testing in the present study versus run-specific testing in the study by Sandbaek et al (1997)). Nevertheless, as intervention studies of moderately trained individuals (pre-training relative VO 2max of ~50-60 ml•kg −1 •min −1 ) indicate that exercise intensities >85% HR max are necessary to affect absolute VO 2max significantly (Helgerud et al, 2007;Jarstad & Mamen, 2019), it is not to be expected that recreational athletes with high aerobic fitness (pretraining relative VO 2max of ≥60 ml•kg −1 •min −1 ) would improve absolute VO 2max following low-intensity exercise around 60% HR max .…”
Section: Vo 2maxmentioning
confidence: 99%